Formative Assessment: Revisiting the territory from the point of view of teachers - Morrissette, Joëlle (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2011)
This research documented the know-how of five elementary-school teachers regarding formative assessment, working from their point of view on the question. Group interviews gave them the opportunity to negotiate their “ways of doing things,” by revisiting and elaborating upon assessment episodes that had been previously identified on classroom videotapes. An interactionist analysis served to describe the territory of formative assessment according to the range of their formal and informal “ways of doing things.”